Critical review: Grand challenges in assessing the adverse effects of contaminants of emerging concern on aquatic food webs. (20th December 2018) - Nilsen, Elena; Smalling, Kelly L.; Ahrens, Lutz; Gros, Meritxell; Miglioranza, Karina S.B.; Picó, Yolanda; Schoenfuss, Heiko L.
Abstract: Much progress has been made in the past few decades in understanding the sources, transport, fate, and biological effects of contaminants of emerging concern (CECs) in aquatic ecosystems. Despite these advancements, significant obstacles still prevent comprehensive assessments of the environmental risks associated with the presence of CECs. Many of these obstacles center around the extrapolation of effects of single chemicals observed in the laboratory or effects found in individual organisms or species in the field to impacts of multiple stressors on aquatic food webs. In the present review, we identify 5 challenges that must be addressed to promote studies of CECs from singular exposure events to multispecies aquatic food web interactions. There needs to be: 1) more detailed information on the complexity of mixtures of CECs in the aquatic environment, 2) a greater understanding of the sublethal effects of CECs on a wide range of aquatic organisms, 3) an ascertaining of the biological consequences of variable duration CEC exposures within and across generations in aquatic species, 4) a linkage of multiple stressors with CEC exposure in aquatic systems, and 5) a documenting of the trophic consequences of CEC exposure across aquatic food webs. We examine the current literature to show how these challenges can be addressed to fill knowledge gaps. Environ Toxicol Chem 2019;38:46–60. © 2018 SETAC